Klasifikasi Parameter Penyebab Kemacetan Jalan Kolektor - Satrio Muhammad Alif; Ruth Angelia Silaen (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2020)
The increasing population in Bandar Lampung has an impact on the increasing traffic congestion. The discussion of the causes of congestion in other studies focuses on the social aspects and there is no comprehensive discussion to determine the main parameters of the congestion causes related to the position of parameters of the body on the road. The study aims to determine the main parameters causing congestion on the collector road related to the position of the parameters of the body on the road using the smallest square modeling. The study took the data from the traffic lights coordinate, railroad tracks, bends, turns, and commercial areas as well as coordinates from the road lines and Google traffic volume. The traffic volume data was taken in the morning, afternoon, and evening on weekdays and weekends for one week. Classification of the congestion causes was based on 65 mathematical equations that were calculated using the smallest square. The congestion happens more likely on weekdays than on weekends. Furthermore, more congestion occurs at night than during the day. The traffic lights are the main parameter causing traffic jams followed by railroad tracks and turns. The rounds with less than 100 meters distance from the traffic lights are recommended to be closed because they cause congestion the most.